2021
DOI: 10.1177/19322968211050649
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Socioeconomic Status, Insurance Coverage for Diabetes Technology and Adverse Health in Patients With Type 1 Diabetes

Abstract: Introduction: Insulin pumps and continuous glucose monitors (CGM) have many benefits in the management of type 1 diabetes. Unfortunately disparities in technology access occur in groups with increased risk for adverse effects (eg, low socioeconomic status [SES], public insurance). Research Design & Methods: Using 2015 to 2016 data from 4,895 participants from the T1D Exchange Registry, a structural equation model (SEM) was fit to explore the hypothesized direct and indirect relationships between SES, insur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…We hope that innovations, such as holistic, integrated care, and tools, such as continuous glucose monitors and insulin pumps, will help to erase these disparities. At the time of this writing, there are inequitable policies and prerequisites to obtain these supportive technologies that have been shown to improve A1c results and decrease adverse health outcomes (Everett & Wisk, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We hope that innovations, such as holistic, integrated care, and tools, such as continuous glucose monitors and insulin pumps, will help to erase these disparities. At the time of this writing, there are inequitable policies and prerequisites to obtain these supportive technologies that have been shown to improve A1c results and decrease adverse health outcomes (Everett & Wisk, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Remote care for T1D hinges on the ability to access patient-generated health data from continuous glucose monitoring (CGM) devices and insulin pumps, but disparities in use of such therapeutic technology persist. 16 -20,24 -26 Health insurance plans must universally cover CGM and insulin pump devices—now recommended as treatment options for people of all ages 82,83 —as a first step. Government policies are needed in parallel to expand broadband Internet access—no longer a luxury but now a strong determinant of outcomes in both health 84 and education 85 —which would enable remote data-sharing as well as synchronous telehealth interactions.…”
Section: Discussionmentioning
confidence: 99%
“…15 Disparities in access to therapeutic technology and health outcomes based on income and race/ethnicity are well-documented for people with T1D. [16][17][18][19][20][21][22][23][24][25][26] In addition, T1D care is well-suited to telehealth due to its reliance on patient-generated health data and behavioral health coaching; for this reason, telehealth was employed for T1D management even prior to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…30 Regarding adults, recent studies from the USA have reported lower CSII and CGM use in patients of all ages with lower SES or less generous insurance. 13,14,31 In New Zealand lower SES was also associated with lower CSII use in patients of all ages. 12 Moreover, a study from the United Kingdom evaluated the use of diabetes technology in adults and found less frequent use in participants from the most deprived neighbourhoods.…”
Section: Sexmentioning
confidence: 97%